Development, validation and application to real samples of a liquid chromatography with tandem mass spectrometry method for the determination of tetracyclines in beeswax. Issue 20 (23rd September 2018) - Gajda, Anna; Antczak, Maja; Mitrowska, Kamila; Posyniak, Andrzej
Abstract: Beeswax is a valuable honeybee product, which finds applications in the food and pharmaceutical industries, as well as in cosmetic production. However, some substances used in apiculture, like tetracyclines, can be delivered to hives where they cause contamination of honeybee products such as beeswax. Tetracyclines are commonly used for the treatment of American and European foulbrood diseases, but in the European Union their usage by beekeepers is forbidden. Thus, a sensitive method for the analysis of tetracyclines in beeswax is an important analytical tool. A new liquid chromatography with tandem mass spectrometry method for the analysis of tetracyclines including oxytetracycline, 4‐epioxytetracycline, tetracycline, 4‐epitetracycline, chlorotetracycline, 4‐epichlorotetracycline, and doxycycline in beeswax was developed. The method involved dilution of beeswax in n ‐hexane after a melting step, liquid‐liquid extraction with oxalic acid and clean‐up using a weak cation exchange phase. Satisfactory separation was performed on an octadecyl column with 0.1% formic acid and acetonitrile in a total run time of 5 min. The application of this method was evaluated by the analysis of real beeswax samples. The presence of oxytetracycline was confirmed in 5 out of 48 tested beeswax samples, which shows the method can be successfully used to determine the tetracyclines in beeswax.